Analisis Pengaruh Desain Produk, Analisis Pengaruh Desain Produk, Harga, dan Promosi terhadap Minat Beli Konsumen Studi Kasus Percetakan Seventeen: Analisis Pengaruh Desain Produk, Harga, dan Promosi terhadap Minat Beli Konsumen Studi Kasus Percetakan Seventeen - Tukiman, Hellena Indriani; Bambang Sumantri, R Bagus (Jurnal Teknologi dan Bisnis, 2020)
Abstract - Design services are the main components in the business and design world that will be generated by an image project that has been created. This is not separated from the role of design applications used such as: Coreldraw, Photoshop. In general, there are several criteria that affect it. This research aims to prioritize the selection of product design, price and promotion services analysis in printing media with Hypothesis Method. The criteria specified there are seven criteria, namely quality, price, and promotion. The purpose of the research is to know the development of printing every year, and the results of the study also want to know how the process of making the design, In addition, the design of the product can form or attribute to a product, so that it can be a characteristic in the brand of a product. The distinctive features of such a product will eventually be able to distinguish it from other similar brands from competitors. So that it can be d ... Keywords : Product Design, Consumer buying interest, Price, Promotion, Hipotesis